POPULISM TO THE LEFT: Democratisation and class consciousness - Vranic, Bojan M (Politeia, 2019)
This paper analyses the possibility of left populism to trigger class consciousness with what Laclau calls populist subjects. The author argues that populist subjects and class consciousness are not identical nor interchangeable concepts in respect to the classical Marx and Engels notion on the proletarian class. In the first part of the paper, the author sets a description of populism based on its three key features: reaction, the notion of the people, and the struggle. In the second part, the idea of class consciousness is analysed, showing that class consciousness is necessarily political. In the third part of the paper, the idea of left populism is explored by using the findings of the second part of the paper, showing structural inconsistencies in the idea of the populist subject.
Keywords: Populism; class consciousness; Marx; Engels; Laclau